Comparison of the Efficacy of Reoperation, Percutaneous Radiofrequency Thermocoagulation When Microvascular Decompression of Trigeminal Neuralgia Is Invalid. Issue 7 (October 2016) - Zhang, Xin; Zhao, Hua; Tang, Yinda; Zhu, Jin; Wang, Xuhui; Li, Shiting
Abstract : Objective: To compare the curative effect of reoperation in short-term and percutaneous radiofrequency thermocoagulation (PRT) when trigeminal neuralgia patient after microvascular decompression (MVD) is invalid. Methods: Follow-up of 54 patients (30 patients with reoperation in the short term, 24 patients with PRT of primitive trigeminal neuralgia) when MVD is invalid between January 2008 and December 2014. To evaluate the degree of pain relief and facial numbness of patients after the treatment in short-term (1 month), in long-term (1 year). Result: One month after surgery, the authors compared the reoperation group with PRT group. The ratio of cure rate P = 0.02, the ratio of effective rate P = 0.04, the ratio of facial numbness P = 0.01; 1 year after surgery, the authors compared the reoperation group with PRT group. The ratio of cure rate P = 0.004, the ratio of effective rate P = 0.006, the ratio of facial numbness P = 0.02, the ratio of recurrence P = 0.04. The short-term and long-term clinical efficacy in reoperation group was better than PRT group ( P < 0.05). Conclusion: For the patients of trigeminal neuralgia when first MVD is invalid, reoperation is better than PRT, and a significantly lower incidence of facial numbness and recurrence than PRT.